SPEAKING DIFFICULTIES AMONG EFL LEARNERS IN A BILINGUAL SCHOOL SETTING - Hidayati, Fitri (2014)
In Indonesia, the English language is not only taught in public schools or through courses but also used as classroom instruction in Bilingual schools. Students in a bilingual school are encouraged to have better English skills. They may also face problems in their English, especially in speaking skill. The present study aimed at investigating the speaking difficulties encountered by EFL learners in Bilingual school setting as well as their abilities. The perception towards the role of bilingual school in improving their English speaking skills was also figured out. The research was conducted in a Bilingual school in Bandung with the participants of 15 students from 10th grade. A qualitative method was employed in this research. The instruments used in the research were speaking performance test, interview, as well as observation. The result showed that the main difficulties in speaking encountered by the students were: grammar, the lack of vocabulary, pronunciation, and nervousness or anxiety. It is expected that this study would give a marked benefit to English teachers in enhancing the knowledge on the difficulties that students face in their speaking performances.;--- Di Indonesia, Bahasa Inggris tidak hanya diajarkan di sekolah umum ataupun kursus tetapi juga digunakan sebagai instruksi kelas di sekolah bilingual. Siswa-siswa di sekolah bilingual diharuskan untuk memiliki kemampuan Bahasa Inggris yang baik. Siswa-siswa tersebut juga mungkin memiliki kesulitan dalam berbahasa Inggris terutama dalam kemampuan berbicara. Penelitian ini bertujuan untuk menganalisis kesulitan yang dihadapi para siswa di sekolah bilingual dan juga untuk mengetahui apakah sekolah bilingual dapat meningkatkan kemampuan berbicara bahasa Inggris para siswa. Penelitian ini merupakan penelitian kualitatif yang menggunakan instrument yaitu: tes performa berbicara bahasa Inggris, interview, dan observasi. Hasil penelitian menunjukkan bahwa para siswa mengalami kesulitan dalam tata bahasa (grammar), kurangnya pengetahuan kosakata (the lack vocabulary), pengucapan (Pronunciation), dan anxiety. Penelitian ini diharapkan dapat berguna untuk memperluas pengetahuan para guru akan kesulitan berbicara bahasa Inggris yang dihadapi para siswa.